Examining the research/teaching nexus. Issue 4 (1st October 2016) - Tight, Malcolm
ABSTRACT: The idea of the research/teaching nexus has become of increasing importance in thinking about higher education over the last three decades. In essence, this idea recognizes the two key functions of higher education – teaching and research – and argues that they are, or should be, closely linked. This article explores the derivation and development of this idea, and considers its application and critique, through a systematic review of the literature. It concludes that, while there is clearly a linkage between research and teaching at a global level, it needs nurturing locally. We might do well to limit the emotional commitment often embodied in thinking about the association between research and teaching, and do more to explore in detail what actually happens in practice.